Characteristics of Marine Litters in the West Coast of Bali - Semeidi Husrin; Ulung Jantama Wisha; Rahmadi Prasetyo; Aprizon Putra; Adli Attamimi (Pusat Riset Kelautan, 2017)
Kuta beach in Bali is a world-famous tourist destination has been suffering from marine litters (or debris) disaster almost every year. Mitigation efforts have been carried out by the local government started from educating the people as well as continuing mass cleaning campaigns for the stranded litters in the beach. The research has an objective to understand the physical processes of marine debris characteristics in Kuta such as its propagation and distribution along the coastline and in the water columns during the two different seasons (West Monsoon and Transitional seasons). A hydrodynamic model was developed to investigate the transport of marine litters from their sources by considering the tide-driven surface currents and wind. Field surveys were also conducted to assess marine litter’s characteristics in the surface and in the sea beds for both plastic and wood types of litters. Hydrodynamic simulation shows that the surface current ranging from 0.05 – 1.75 m/s is capable of transporting marine surface debris from Bali Straits and other sources in the South of Bali to Kuta during West Monsoon season. The collected litters during the West Monsoon season were four times larger in quantity. The concentration of litters in the seabed and in the water column is larger near to the coastline than further offshore. In the meantime, during Transitional season, Kuta was completely free from marine litters. Results from surveys also showed that the most effective measures for marine litters in Kuta is self-awareness of the people to keep the environment clean.